Akustische Phonetik und ihre multidisziplinären Aspekte (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
The aim of this book is to honor the multidisciplinary work of Doz. Dr. Sylvia Moosmüller† in the field of acoustic phonetics. The essays in this volume range from sociophonetics, language diagnostics, dialectology, to language technology. They thus exemplify the breadth of acoustic phonetics, which has been shaped by influences from the humanities and technical sciences since its beginnings.